High potential for weathering and climate effects of non-vascular vegetation in the Late Ordovician - P. Porada (Nature Portfolio, 2016)
Early non-vascular vegetation may have caused an interval of glaciations in the Late Ordovician by enhancing global chemical weathering. Here, by simulating the organisms with a spatially explicit, process-based model, the authors propose that Ordovician vegetation had a high potential for chemical weathering.